The effects of Juglans regia L. (walnut) extract on certain biochemical paramaters and in the prevention of tissue damage in brain, kidney, and liver in CCl4 applied Wistar rats - Aydin, Sevinc; Gokce, Zehra; Yilmaz, Okkes (Walter de Gruyter Gmbh, 2015)
Objective: The purpose of this study is to demonstrate protective effects of walnut samples on CCl4 induced tissue damage in vivo. Methods: Walnut fruits were extracted and then subjected to vitamin and flavonoid analyses. The extracts obtained were injected intraperitoneally every other day to Wistar male rats given carbon tetrachloride (CCl4) and the animals were decapitated at the end of the study period. The brain, kidney, and liver tissues were removed and lipid peroxidation (LPO) measurements were done in the lipid fraction generated. The fatty acids in the lipid extract were analyzed by gas chromatography after converting them into methyl esters. In addition, the amounts of glutathione, protein, and vitamins were analyzed. Results: Given the results achieved, it was found that the levels of fatty acids increased in the brain and kidney tissues after CCl4 administration (p<0.001). In the groups given walnut extract against CCl4, it was found that the glutathione (GSH) level increased and malondialdehyde (MDA) level reduced in all tissues (p<0.05, p<0.01). Given lipophilic vitamin levels, it was found that a-tocopherol level increased in the brain and liver tissues in the group receiving additional walnut in comparison with the controls (p<0.05), and cholesterol level increased in the tissues, except kidney, in all groups in comparison with the control group (p<0.05, p<0.001). Conclusion: Our data indicates that walnut extract has protective effects against LPO formation in the brain, kidney and liver tissues.
CCl4 uygulanan Wistar sıçanlarda beyin, böbrek ve karaciğer doku hasarlarının önlenmesinde ve bazı biyokimyasal parametreler üzerine Juglans regia L. (ceviz) ekstraktının etkileri
Keywords: Juglans regia L.; lipid peroxidation (LPO); antioxidant; MDA; CCl4